POTENSI LOGAM OKSIDA SEBAGAI FOTOKATALIS DEGRADASI PLASTIK DI AIR LAUT - Muhammad Safaat (OSEANA, 2020)
Microplastics have been found in Indonesian seas from surface to sediments with varying amounts, sizes and shapes. Microplastics in surface and sediments can negatively affect biota. Microplastic can stick to the surface and enter the marine biota through direct consumption, inhalation, and trophic transfer. A number of approaches have been proposed to deal with the plastic debris. This includes combustion, thermal degradation, biodegradation and photocatalysis. A nanostructure photocatalyst can be an environmentally friendly way to fix the problem of plastic debris. Metals can catalyze dissociation of hydroperoxides and increase oxidative cutting of polyolefins. In this review, we want to assess the feasibility of metal oxides as photocatalysts for plastic degradation, especially in seawater. Metal oxides can catalyze plastic degradation and form several compounds along the chain, such as hydroxyl (alcohol), peroxide, carbonyl groups, esters, and low molecular weight molecules. In general, metal oxide modification can increase the effectiveness of the plastic degradation photocatalytic process.